A theoretical and empirical analysis of the influence of socio-psychological factors on young people’s assessment and self-assessment of appearance - Vera А. Labunskaya; Irina I. Drozdova (Rossijskij psihologičeskij žurnal., 2017)
Introduction.The interpretation of appearance, its assessment and self-assessment in terms of socio-psychological approach.The paper develops a socio-psychological approach to appearance, its assessment, and self-assessment. Appearance is the constructed form of objectification of the inner world of a person. This is the phenomenon that reflects various stages of a life path in accordance with dynamic and variable interrelations among the following three components: (a) physical; (b) social appearance; (c) expressive behavior. The socio-psychological approach to appearance treats assessment and self-assessment as results of the socio-perceptual activity that establishes associations among appearance, psychological, and socio-psychological characteristics of the person. Young people’s assessment and self-assessment of appearance are significant, emotionally saturated phenomena, which enter the sense-value sphere and regulate experiences and relations of young people. Socio-cultural and socio-psychological factors of assessment and self-assessment of appearance.Assessment and self-assessment of appearance depended on a great number of various factors. The study examined socio-psychological factors of assessment and self-assessment of appearance of significant others, a family, and a group, which often exert “social pressure” on young people’s attitude towards their own appearance. The findings highlighted the integral socio-psychological, personal factors (self-relation, life strategies, life satisfaction, perfectionism, narcissism) of the dynamics of assessment and self-assessment of appearance. Discussion and justification for the “multi-factor socio-psychological model for studying attitudes towards appearance”. On the basis of the socio-psychological analysis of the problem of assessment and self-assessment of appearance the study concludes that the correlation approach predominates in the studies. In the study of assessment of appearance, one-, two-, and three-factor models should be changed by a “multi-factor socio-psychological model for studying the attitude towards appearance”. This model includes the following factors: (a) components of appearance (physical, social appearance, expressive behavior) and their integral characteristics; (b) group, interpersonal, personal, and subjective factors mediated by socio-cultural conditions of a person’s being.